The impact of Monetary- Fiscal Policy on Economic growth: Empirical Evidence from Iraq 1970-2017 - Khan, Twana Najaf Mohammed (Salam (Islamic Economics Journal), 2024)
Most of the studies in the literature focused on the impact of monetary or fiscal policy on economic growth. However, this article combined the efficiency of both policies (fiscal and monetary) on economic growth in Iraq for the period 1970 to 2017 using the Autoregressive Distribution Lag (ARDL) model and Granger Causality techniques. The annual data included in the model were Gross Domestic Product (GDP) as a proxy of economic growth, government expenditure, and broad money as a proxy of fiscal-monetary policy and trade openness as a controlling variable. Results obtained from the analysis showed a positive long-run relationship between fiscal policy and economic growth in Iraq. At the same time, negative significant impacts were recorded from monetary policy to economic growth. Furthermore, the study discovered unidirectional causality from government expenditure to economic growth. Otherwise, there is no causality between money supply and economic growth.